1995
DOI: 10.1177/104973159500500104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a School-Based Child Abuse Prevention Program

Abstract: This article reports the results of an evaluation study of a school-based educational child abuse prevention program using a quasi-expetimental design. Seven hundred ninety-six (796) children, both male and female, at three grade levels, and from nine public and parochial schools participated in the study. Following the presentation of the educational program, an impressive increase in the posttest mean score on a child abuse questionnaire of the treatment group occurred, differences between the posttest mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 8 publications
2
22
0
2
Order By: Relevance
“…This suggests that the students' self-ratings of their knowledge was more a reflection of an adolescent "I know everything" response bias than their actual information. Thus, this study confirmed what others (e.g., Dhooper & Schneider, 1995) have found; that is, most students have a core of common knowledge about abuse, but students who participate in abuse prevention programs have greater understanding of subtle, yet important, issues. These issues included attribution of blame, understanding that abusers could be people who are close to the victim, awareness that both girls and boys could be victims, and acknowledging the need to report abuse.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests that the students' self-ratings of their knowledge was more a reflection of an adolescent "I know everything" response bias than their actual information. Thus, this study confirmed what others (e.g., Dhooper & Schneider, 1995) have found; that is, most students have a core of common knowledge about abuse, but students who participate in abuse prevention programs have greater understanding of subtle, yet important, issues. These issues included attribution of blame, understanding that abusers could be people who are close to the victim, awareness that both girls and boys could be victims, and acknowledging the need to report abuse.…”
Section: Discussionsupporting
confidence: 89%
“…Again, no statistically significant difference between groups emerged, F(1, 136) ϭ .73 (ns). Other studies (e.g., Dhooper & Schneider, 1995) had found that many children had general knowledge about abuse, but that children who participated in prevention programs gained in specific areas of knowledge covered by the program. A subset of 4 items was identified on our questionnaire that covered issues specific to the program (items ࠻1, 4, 6, and 7; see Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…Student disclosures indicated a wide range of inappropriate sexual experiences, i.e., grooming, rape, sexual assault, sexual harassment, child sexual abuse, and erotica. In comparison disclosure levels for sexual abuse in previous efficacy studies ranged from 0.3% (Dhooper and Schneider 1995) to 6.5% Pohl and Hazzard 1990), with an average of 2.75% from six studies (Pohl and Hazzard 1990; Hazzard et al 1991; Madak and Berg 1992; Briggs and Hawkins 1994a, b; Dhooper and Schneider 1995; Oldfield et al 1996). Some of the reasons for these differences may include differing child protection procedures, definitions, levels of training, and awareness of participants and design methodology.…”
Section: Discussionmentioning
confidence: 85%
“…Many studies gave overall disclosure rates for experimental and control groups or reported that disclosures occurred but gave no figures, e.g., Dhooper and Schneider (1995). Where disclosures were reported percentages were small in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence and prevalence statistics over the last two decades indicated that child sexual abuse was a significant issue for society occurring across all socio-economic levels and in all ethnic groups (Dhooper and Schneider, 1995). Cicchetti and Toth (1995) highlighted the immediate and long-term consequences of abuse and the subsequent impact on the psychosocial development of children including depression,…”
Section: Introductionmentioning
confidence: 99%